Emergencies Hypertensive: A long term follow-up of renal function with pharmacological and Non Pharmacological therapy - Tiziana Ciarambino; Mauro Giordano (Archives of Clinical Hypertension - Peertechz Publications, 2019)
Background: Patients who experience emergencies (HEs) and urgencies (HUs) hypertensive are at high risk for developing clinical complications such as ischemic attack, acute renal injury, or any other ischemic organ damage. Methods: We reported a case of 45 year-old female admitted to our Emergency Medicine Department for cefalea. The clinical characteristics at admission were: BP was 220/125 mmHg, HR 90 bpm, SO2 92% A.A., no fever, BMI 25 kg/m2. She received a treatment with intravenous labetalolo 20 mg BID, followed by 20 mg after 20 minutes. After about 6 hours she was asymptomatic and blood pressure was 150/90 mmHg. We invited to take enalapril 20 mg and she started low protein diet (LPD) (0.8 gr/Kg/day) at home. Conclusion: Our approach might be to add pharmacological therapy with LPD for patient with HEs and acute renal failure. In fact, it has been reported that LPD retard the progression of renal failure.